Analisis Komparatif Subjective Well-Being Remaja Ditinjau dari Perspektif Gender - Salsabila Nasution; Ade Herdian Putra; Dwi Endrasto Wibowo (International Journal of Applied Counseling and Social Sciences, 2025)
Subjective Well-Being (SWB) refers to an individual's assessment of their life satisfaction and emotional well-being. In adolescents, SWB is strongly influenced by various factors, including social relationships, family conditions, and academic and personal experiences. A good level of SWB in adolescents can contribute to healthy psychological development and the ability to overcome complex life challenges. This study aims to analyze the level of Subjective Well-Being (SWB) of adolescents in Medan City from a gender perspective. The sample of this study consisted of 100 adolescents divided into 33 males and 67 females. The instrument used in this study was the condition questionnaire from Pontin (2013) which consists of 13 items to measure adolescent SWB. The data obtained were analyzed using SPSS and Excel with the Kruskal-Wallis test, because the data were not normally distributed. The results showed that 26% of adolescents had low SWB, 52% were in the medium SWB category, and 22% had high SWB. The Kruskal-Wallis test showed no significant difference between the SWB levels of male and female adolescents (Asymp. Sig. = 0.662). This study concluded that gender does not significantly influence SWB of adolescents in Medan City, although there are variations in the levels of SWB experienced by adolescents. The limitations of this study lie in the small sample size and the use of a single instrument, so further research with a larger sample and additional variables is needed to obtain a more comprehensive picture of adolescent SWB.